2018
DOI: 10.1111/pce.13318
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration directly regulates the emissions of water‐soluble short‐chained OVOCs

Abstract: Most plant-based emissions of volatile organic compounds are considered mainly temperature dependent. However, certain oxygenated volatile organic compounds (OVOCs) have high water solubility; thus, also stomatal conductance could regulate their emissions from shoots. Due to their water solubility and sources in stem and roots, it has also been suggested that their emissions could be affected by transport in the xylem sap. Yet further understanding on the role of transport has been lacking until present. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…Radon is a natural tracer with a wide variety of applications to tree‐gas research including studies of greenhouse gas emissions (Fig. ), volatile organic carbon emissions (Rissanen et al ., ), hypoxia effects on physiology and development (Spicer & Holbrook, ), and forest regulation of aerosol production (Jayaratne et al ., ). Patterns in stem radon emissions across species, seasons, and diurnal periods suggested that tree transport of soil‐produced and plant‐produced gases is controlled by plant hydraulics, and that trees emit soil gases during the night when transpiration rates are negligible.…”
Section: Resultsmentioning
confidence: 99%
“…Radon is a natural tracer with a wide variety of applications to tree‐gas research including studies of greenhouse gas emissions (Fig. ), volatile organic carbon emissions (Rissanen et al ., ), hypoxia effects on physiology and development (Spicer & Holbrook, ), and forest regulation of aerosol production (Jayaratne et al ., ). Patterns in stem radon emissions across species, seasons, and diurnal periods suggested that tree transport of soil‐produced and plant‐produced gases is controlled by plant hydraulics, and that trees emit soil gases during the night when transpiration rates are negligible.…”
Section: Resultsmentioning
confidence: 99%
“…In trees, methanol production is connected to growth and is produced mainly in leaves and needles in spring, and in stem and root expansion in summer. Soil VOC production can also influence the canopy fluxes, because methanol produced in the stem and roots during their growth, can be transported to the canopy via transpiration stream (Rissanen et al, 2018), and hence be emitted through stomata (Folkers et al, 2008). Peaking acetone and acetaldehyde fluxes above a hardwood forest in autumn were speculated to result from leaf senescence and decaying biomass (Karl et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…During the day, they can fluctuate rapidly, in response to changes in cloud cover and shading by the canopy (Singsaas and Sharkey, 1998). Light influence on stomatal conductance constrains emissions of polar water-soluble VPCs such as methanol, which can be further modified by diurnal changes in transpiration and water transport (Rissanen et al, 2018). On the other hand, emissions of apolar hydrophobic VPCs are independent of stomatal conductance, even though these VPCs diffuse principally through stomata (Niinemets et al, 2002).…”
Section: Temporal Aspects: the Dynamics Of The Odorscapementioning
confidence: 99%